The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1139/l08-109
|View full text |Cite
|
Sign up to set email alerts
|

Safety performance of longer combination vehicles relative to other articulated trucks

Abstract: This article helps improve the understanding about the safety performance of longer combination vehicles (LCVs) relative to other articulated trucks operating on rural highways, using evidence from the Canadian portion of the CANAMEX trade corridor. The analysis reveals that from a collision rate perspective, LCVs as a group have better safety performance than other articulated trucks. Turnpike doubles have the lowest collision rate of all articulated truck types (16 collisions per 100 million vehicle-kilometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Studies have shown 87, (88), (89) that the safety performance of LCVs operating under special permit in Canada has been very encouraging when compared with tractor semitrailers. Turnpike doubles have the lowest crash rate of all LCVs, between 2.5 and 5 times less than standard tractor semitrailers (87), (88), (89), (90). LCVs also have significant environmental benefits due to the improved efficiency of the vehicles.…”
Section: Lcv Operationsmentioning
confidence: 99%
“…Studies have shown 87, (88), (89) that the safety performance of LCVs operating under special permit in Canada has been very encouraging when compared with tractor semitrailers. Turnpike doubles have the lowest crash rate of all LCVs, between 2.5 and 5 times less than standard tractor semitrailers (87), (88), (89), (90). LCVs also have significant environmental benefits due to the improved efficiency of the vehicles.…”
Section: Lcv Operationsmentioning
confidence: 99%
“…Based on a survey of LCV carriers, Nix (1995) estimates that total annual LCV travel in Alberta, Saskatchewan, Manitoba, and Québec (the four provinces that permitted LCVs at the time) amounted to 71 million kilometres. In Alberta, Regehr et al (2009b) As the LCV network expands and LCV operations grow, the need for inter-jurisdictional regulatory harmonization has become apparent. The recent (2012) memorandum of understanding (MoU) signed by the four western provinces (i.e., British Columbia, Alberta, Saskatchewan, and Manitoba) demonstrates a desire to create a seamless operating environment for inter-jurisdictional LCV activity.…”
Section: Overview Of Lcv Operations In Canadamentioning
confidence: 99%
“…That is, while it enabled intra-jurisdictional movements (e.g., between Calgary and Edmonton, Alberta; between Regina and Saskatoon, Saskatchewan; between Winnipeg and Brandon, Manitoba), gaps in the network precluded significant levels of inter-jurisdictional LCV movement. As these gaps were closed, however, available evidence shows a corresponding increase in the levels of LCV activity in the region (Regehr 2009;Regehr, Montufar, and Clayton 2009a;Regehr et al 2009b;Di Cristoforo et al 2012).…”
Section: Network Connectivity and Inter-jurisdictional Regulatory Harmentioning
confidence: 99%
“…These characteristics are fundamental inputs to nearly all aspects of highway engineering. Principal examples are: the analysis of traffic operations impacts of articulated trucks and the related design of road geometry (Harkey et al 1996;Elefteriadou et al 1997); the development and use of load spectra for mechanisticempirical pavement design (Hajek et al 2002;AASHTO 2008), and the design and evaluation of bridge structures (Ghosn and Moses 2000;National Cooperative Highway Research Program 2003); the determination of the safety performance of articulated trucks in terms of collision rates (Regehr et al 2009); and the analysis of energy, fuel, and emissions impacts of different types of articulated trucks (ATRI 2008).…”
Section: Implications For Network Planning and Highway Engineeringmentioning
confidence: 99%